Have Racial and Ethnic Disparities in Juvenile Justice Declined Over Time? An Empirical Assessment of the DMC Mandate - Zane, Steven N. (Youth violence and juvenile justice, 2021)
The present study examines whether racial and ethnic disparities in juvenile justice declined significantly in a state that has made substantial reform efforts in compliance with the Disproportionate Minority Contact (DMC) mandate. Using a sample of all referrals in Connecticut with final disposition in 2000 (N = 18,458) or 2010 (N = 12,265), the study employed multilevel modeling with cross-level interactions to assess whether disparities changed over time for five outcomes: detention, petition, adjudication, commitment, and waiver to criminal court. Findings indicated that Black-White disparities in detention decreased over time, while Black-White disparities increased for petition, adjudication, and waiver. Findings also indicated that Hispanic-White disparities increased for adjudication (while not changing for other outcomes). The limited success of the DMC mandate may be explained by implementation failure or theory failure. Adjudicating between these alternative explanations is needed to guide future reform efforts. Several implications for research and policy are discussed, including whether reform efforts should focus on overall harm reduction rather than proportional representation.